Targeting mitochondrial dysfunction in the treatment of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) - a clinical audit - Myhill, Sarah (e-Century Publishing Corporation, 2012)
We report on an audit of 138 ME/CFS patients who attended a private practice and took the ATP Profile biomedical test. The results revealed that all of these patients had measureable mitochondrial dysfunction. A basic treatment regime, based on 1) eating the evolutionary correct stone-age diet, 2) ensuring optimum hours of good quality sleep, 3) taking a standard package of nutritional supplements, and 4) getting the right balance between work and rest, was recommended for all patients. Additions to the basic regime were tailored for each patient according to the results of the ATP Profile and additional nutritional tests and clues from the clinical history. Mitochondrial function is typically impaired in two ways: substrate or co-factor deficiency, and inhibition by chemicals, exogenous or endogenous. For the former, additional nutrients are recommended where there is a deficiency, and for the latter, improvement of anti-oxidant status and selective chelation therapy or far-infrared saunas are appropriate. We show case histories of nine patients who have taken the ATP Profile on three or four occasions, and a before-and-after treatment summary of the 34 patients who have had at least two ATP Profile tests separated by some months. Finally, we summarize the results for the 30 patients who followed all aspects of the treatment regime and compare them with the 4 patients who were lax on two or more aspects of the treatment regime. All patients who followed the treatment regime improved in mitochondrial function by on average a factor of 4.